A conservação natural como parâmetro para o planejamento do território : aplicação dos princípios da ecologia de paisagem em área de expansão urbana no município de São João da Boa Vista, SP - Araújo, Leandro Letti da Silva (2010)
Landscape appropriation, occupation and management processes currently used by human beings have generated conflicts which may lead to environmental quality deterioration. In face of its constant development and the need for territorial expansion, new planning models must be proposed considering as main premise the maintenance of environmental integrity and maximization of available scenic resources. Based on scenery ecology, this research discusses the elements of landscape and the importance of integrating ecological concepts in territorial process undertaken by humans. As a case study, an area from the municipal district of São João da Boa Vista in São Paulo state, with potential for urban expansion and conservation of important remaining fragments of seasonal semideciduous forest belonging to the atlantic forest biome, was selected. The study area was chosen based on its biophysical characteristics, use and land occupation, which occur throughout the district, allowing the expansion of the resulting proposal to other areas. Anthropogenic and natural biotopes identification and characterization, which compose the study area scenery mosaic, were conducted using Geographic Information Systems (ArcGIS 9.2 ESRI) in order to unify the information gathered in field surveys, scientific research and satellite image interpretation. Afterwards, thematic maps were generated assisting the accomplishment of a preliminary study aimed to integrate planning between anthropic and natural environment. Starting from the conservation principle, reasonable and sustainable use of natural resources, four spaces were proposed with specific use levels: protection of environmental resources, connectivity, buffering and interaction between humans and nature. As a result, a thematic map was developed with the desired environmental scenario, providing guidelines to decision makers and civil society in order to conduct municipal planning along with environmental responsibility.